Probabilistic Differential Diagnosis of Auditory Dysfunction on the Basis of Electrocochleography - Hermans, J.; Eggermont, J. J.; Hagedooren, J.; Odenthal, D. W. (Methods of Information in Medicine, 1975)
Bayes’ theorem was used to establish a probabilistic differential diagnosis between four hearing states :normal hearing, conduction hearing loss, Menière’s disease, and hair-cell damage. Measurements were carried out by electrocochleography (ECoG), action potentials being determined in response to short tone-burst stimulation. This method proved to permit differentiation between normal and abnormal cochleas, but the present state of development does not allow a more detailed diagnosis.
Keywords: Bayes’ Theorem; robabilistic Differential Diagnosis; Electrocochleography